UV-LED as a new emerging tool for curable polyurethane acrylate hydrophobic coating - Ghazali, Siti Khairunisah; Adrus, Nadia; A. Majid, Rohah; Ali, Fathilah; Jamaluddin, Jamarosliza (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The elimination of mercury, low energy consumption, and low heat make the ultraviolet light-emitting diode (UV-LED) system emerge as a promising alternative to conventional UV-mercury radiation coating. Hence, a series of hydrophobic coatings based on urethane acrylate oligomer and fluorinated monomer via UV-LED photopolymerisation was designed in this paper. The presence of fluorine component at 1160 cm−1, 1235 cm−1, and 1296 cm−1 was confirmed by Fourier Transform Infra-Red spectroscopy. A considerably high degree C=C conversion (96–98%) and gel fraction (95–93%) verified the application of UV-LED as a new technique in radiation coating. It is well-accepted that fluorinated monomer can change the surface wettability as the water contact angle of the coating evolved from 88.4° to 121.2°, which, in turn, reduced its surface free energy by 70.5%. Hence, the hydrophobicity of the coating was governed by the migration of the fluorine component to the coating surface as validated by scanning electron and atomic force microscopies. However, above 4 phr of fluorinated monomer, the transparency of the cured coating examined by UV-visible spectroscopy experienced approximately a 16% reduction. In summary, the utilisation of UV-LED was a great initiative to develop green aspect in photopolymerisation, particularly in coating technology